PENGARUH PERSAHABATAN TERHADAP KEAKTIFAN KEGIATAN LITURGI KAUM MUDA DI LINGKUNGAN SANTO PETRUS PAROKI SANTO VINCENTIUS A PAULO MALANG - Gathan` Aryasena; Sri Wahyuni (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2023)
Friends play an important role in everyone's life. Apart from family, usually someone in this case young people will draw a lot of influence both positive and negative from their friends. What is meant in this study is the spiritual friendship of young people in the Saint Petrus Parish of Saint Vincentius a Paulo Malang, especially in the field of liturgy or consecration. Young people in St. Peter's neighborhood participate in many liturgical activities, including participating in community prayer activities, deepening their faith and liturgical activities in the Church as lecturers, psalms and acolytes. The purpose of this study was to see whether there was an influence of friendship on the liveliness of the liturgical activities of young people in the Saint Petrus Parish of Saint Vincentius a Paulo Malang. The sampling technique was purposive sampling, meaning that data was collected using certain criteria, in this case only young people who were truly active in liturgical activities. For the data collection method using the questionnaire method, while the instrument is a questionnaire with a scale of four (4) levels. For closed questionnaires where the researcher has determined the answers so that the respondents just have to choose. Twenty (20) questionnaires were distributed but eighteen (18) were returned. Data collection was carried out in November 2022. From the analysis of the data it turned out that the results were influential, that is, from 18 young people, an average result was obtained of 64.16%. This shows that liturgical activities that are followed and carried out by young people are influential where one young person influences other young people to take part in liturgical activities both in the church and in the environment.